2003
DOI: 10.1002/cncr.11691
|View full text |Cite
|
Sign up to set email alerts
|

The development of bladder tumors and contralateral upper urinary tract tumors after primary transitional cell carcinoma of the upper urinary tract

Abstract: A four objective optimization framework for preferential crystallization of D‐L threonine solution is presented. The objectives are maximization of average crystal size and productivity, and minimization of batch time and the coefficient of variation at the desired purity while respecting design and operating constraints. The cooling rate, enantiomeric excess of the preferred enantiomer, and the mass of seeds are used as the decision variables. The optimization problem is solved by using adaptation of the nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
153
8
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(193 citation statements)
references
References 114 publications
26
153
8
6
Order By: Relevance
“…who have low-grade cancers. 18 Our analysis failed to prove the independent prognostic role of histologic grade, which also happened in other large series. 4,[8][9][10] This may have been caused by the lack of a significant difference in survival between patients with grade 1 tumors and grade 2 tumors and by the lack of significant reproducibility in the diagnosis of grade in TCC.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…who have low-grade cancers. 18 Our analysis failed to prove the independent prognostic role of histologic grade, which also happened in other large series. 4,[8][9][10] This may have been caused by the lack of a significant difference in survival between patients with grade 1 tumors and grade 2 tumors and by the lack of significant reproducibility in the diagnosis of grade in TCC.…”
Section: Discussioncontrasting
confidence: 68%
“…These data were quite original in the literature, because other reports on this issue failed to demonstrate a significant prognostic role in multivariate analysis. 8,18 These features, along with the prognostic role of prior or concomitant bladder cancers, strongly reconfirm the panurothelial nature of the disease. It has been demonstrated that the presence of lymphovascular invasion is an important prognostic factor in other urologic malignancies, including prostate cancer, 21 squamous cell carcinoma of the penis, 22 and bladder TCC.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…La recurrencia de este tipo de tumores es relativamente frecuente. La incidencia de enfermedad pé lvica contralateral es del 3%, la de afectació n vesical del 31,2% y la de enfermedad del uré ter contralateral del 5,8% 5 .…”
Section: Introducció Nunclassified